2023
DOI: 10.1039/d2nr05283k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and degradation mechanism of renally excretable gold core–shell nanoparticles for combined photothermal and photodynamic therapy

Abstract: Photothermal therapy using Zein gold nanoshell as a potent therapeutic aproach in the treatment of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The in vitro photothermal evaluation of the material was evaluated on the MDAMB-231 breast cancer cell line. 36 The cells were seeded in a 96-well plate, which was replaced with the WS 2 material (corresponding to 25 ppm tungsten) dispersed in fresh media after the cells are allowed to attach for 24 h. A 808 nm wavelength laser was irradiated for 5 min at a power of 1 W cm −2 . The cells were incubated with the PEG:WS 2 nanosheets for 24 h, followed by washing with PBS.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The in vitro photothermal evaluation of the material was evaluated on the MDAMB-231 breast cancer cell line. 36 The cells were seeded in a 96-well plate, which was replaced with the WS 2 material (corresponding to 25 ppm tungsten) dispersed in fresh media after the cells are allowed to attach for 24 h. A 808 nm wavelength laser was irradiated for 5 min at a power of 1 W cm −2 . The cells were incubated with the PEG:WS 2 nanosheets for 24 h, followed by washing with PBS.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The next aspect of nanoassemblies biosafety focuses on their excretion pathway and time. [ 2b,204 ] Ideally, the administered nanoparticles will be preferentially excreted from the human body via the renal pathway. This restricts body exposure by minimizing cellular internalization during circulation.…”
Section: Biosafety Profilementioning
confidence: 99%
“…It was however reported that the majority of nanoparticles administered are captured by the MPS of major organs potentially causing severe in vivo toxicity. [ 204 ] The core factors influencing the excretion pathway of nanoassemblies include their size and surface functionality. [ 2b ] Nanoassemblies with a size smaller than 6 nm are mostly excreted via the hepatic pathway (i.e., liver metabolism, bile excretion, and defecation).…”
Section: Biosafety Profilementioning
confidence: 99%
“…According to the findings of the ROS study, laser therapy can lead to the pro-duction of reactive oxygen species ( photodynamic therapy), which may contribute to the increased cancer cell mortality rate. 75…”
Section: Mechanism Of Induced Cell Deathmentioning
confidence: 99%